1989
DOI: 10.1128/jb.171.12.6409-6413.1989
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional regulation of yeast delta-9 fatty acid desaturase activity

Abstract: The addition of unsaturated fatty acids to cultures of Saccharomyces cerevisiae significantly altered the microsomal lipid composition. Supplementation with either of the naturally occurring palmitoleic (16:1) or oleic (18:1) acids caused increased levels in membrane phospholipids and reduced levels of the complementary acid. Growth in the presence of equimolar quantities of 16:1 and 18:1 acids, however, produced a fatty acid composition similar to that found in unsupplemented cell membranes. Linoleic acid (18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
95
0
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(105 citation statements)
references
References 29 publications
8
95
0
2
Order By: Relevance
“…The alternative possibility that oxygen-o r nitrogen-induced covalent modification altered the relative proportion of 'active' enzyme can be discounted here. Firstly, no such mechanism has been reported for desaturases, where regulation is generally considered to occur at the transcriptional o r translational level (Bossie & Martin, 1989;McDonough e t al., 1992;Vigh e t al., 1993). Moreover, it was found that cells which were transiently exposed to elevated oxygen, by chilling cultures just prior to sparging with nitrogen, still displayed considerably higher desaturase activity 1 h later than cells chilled after exposure to nitrogen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alternative possibility that oxygen-o r nitrogen-induced covalent modification altered the relative proportion of 'active' enzyme can be discounted here. Firstly, no such mechanism has been reported for desaturases, where regulation is generally considered to occur at the transcriptional o r translational level (Bossie & Martin, 1989;McDonough e t al., 1992;Vigh e t al., 1993). Moreover, it was found that cells which were transiently exposed to elevated oxygen, by chilling cultures just prior to sparging with nitrogen, still displayed considerably higher desaturase activity 1 h later than cells chilled after exposure to nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…In Saccharomyces cerevisiae, supplementation of growth media with unsaturated fatty acids resulted in a decline in transcription of the desaturase gene (Bossie & Martin, 1989) ; the specificity of this response to particular fatty acid species suggested that regulation was initiated by fatty acid binding to a transcriptional sensor, rather than by changes in membrane order (McDonough e t al., 1992). In the cyanobacterium S'nechoystis PCC 6803, increases in the degree of plasma-membrane fatty acid saturation, brought about by palladium-catalysed hydrogenation, resulted in enhanced transcription of the desA gene encoding the Al2-desaturase in a similar fashion to low-temperature induction (Vigh e t al., 1993 ;Murata, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…OLE1 expression is regulated by fatty acids, oxygen and temperature. Saturated fatty acids induce a 1?6-fold increase in transcription, while unsaturated fatty acids repress OLE1 transcription up to 60-fold (McDonough et al, 1992;Bossie & Martin, 1989). At low temperatures and during oxygen limitation, OLE1 expression is induced (Kwast et al, 1998;Nakagawa et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Desaturation is catalyzed by a single essential ⌬-9 desaturase encoded by the OLE1 gene (Stukey et al, 1989(Stukey et al, , 1990. The activity of the desaturase is tightly regulated at several different levels by UFA levels (Bossie and Martin, 1989). For example, steady state levels of OLE1 mRNA sharply decline upon addition of UFAs by a mechanism that is sensitive to the position of the double bond and that involves both transcriptional and posttranscriptional regulation of OLE1 mRNA synthesis and stability (McDonough et al, 1992;Gonzalez and Martin, 1996;Choi et al, 1996).…”
Section: Introductionmentioning
confidence: 99%